Valoración del riego de desarrollar diabetes Mellitus tipo 2 a través del Test de Findrisk en la población de la cabecera cantonal del cantón Sozoranga. - Muñoz Gualán, Alberth Patricio (2017)
Type 2 Diabetes Mellitus is a chronic disease, characterized by varying degrees of insulin resistance. Although there are multiple causes that trigger this disease, they include certain risk factors, among which we have as most important: age, history of diabetes mellitus in the family, abdominal perimeter, physical activity, inadequate diet, associated arterial hypertension, dysglycemias and body mass index. The objectives of the study were to know the main risk factors for developing type 2 diabetes mellitus, to determine the risk according to age, to determine the risk according to gender, to stablish the general risk and to construct a prevention proposal. It was a quantitative, descriptive, transversal study, being the sample of 210 people of the cantonal head of the canton Sozoranga. The FINDRISK Test, which contains the risk factors mentioned above, is used as a prevention tool. The results showed that 10% of the participants presented moderate risk, 11% presented high risk and 2% presented a high risk. Of the participants, 45.7% were overweight, 21% were obese, and 31% had altered abdominal circumference. The sedentarism was present in 41%. Inadequate food intake in 43.3% of the population. Alterations of the blood pressure in 10.5%. The 11% of the population had a history of dysglycemia. Regarding family history, 28.6% presented them in first-degree relatives, and 21.9% in second-degree relatives. It is concluded that the main risk factors in the study population are abdominal perimeter, sedentary lifestyle, poor diet and overweight; being greater the risk in people between 55 to 64 years, in the masculine gender with the 11% og te population in high risk. Key words: diabetes, risk, FINDRISK.